Review of the highly obscure monotypic genus Ranghana Moore, 1878 with the first description of male from the Sundarbans, Bangladesh (Lepidoptera: Erebidae: Arctiinae) - Rayhan, Md Jahir; Jahan, Sayema; Twaha, Sidratul Muntaaha; Fahim, Md (Zootaxa, 2026)
The obscure Arctiinae genus Ranghana Moore, 1878, is reviewed here. The previously undescribed male of its sole species, Ranghana punctata Moore, 1878, is described and illustrated for the first time, based on material collected from the Sundarbans mangrove forest, Bangladesh. Detailed accounts of the male and female genitalia, along with comprehensive descriptions of the morphology and ecological aspects, are provided and illustrated.